Locked-in Syndrome Due to Metastatic Pontomedullary Tumor: Case Report - INCI, Servet; ÖZGEN, Tuncalp (Neurologia medico-chirurgica, 2003)
A 21-year-old man presented with an extremely rare case of locked-in syndrome caused by a metastatic brainstem tumor manifesting as quadriplegia, lower cranial nerve pareses, and irregular respiration. Cranial magnetic resonance imaging revealed a large pontomedullary tumor. An emergency operation was performed via a posterior fossa approach and the tumor was grossly totally removed. The histological diagnosis was malignant melanoma. The clinical status of the patient remained unchanged and he died on postoperative day 34 of diffuse bronchopneumonia. Locked-in syndrome is characterized by quadriplegia, lower cranial nerve paralysis, and mutism but with maintenance of consciousness, as well as vertical eye movements and eyelid blinking. This case suggests that locked-in syndrome should be considered in any patient seemingly comatose or stuporous, this syndrome may be due to a pontomedullary tumor, and malignant melanoma metastasis should be considered in the differential diagnosis of patients who present with brainstem tumor.